'The shadows of "boundary" remain': curriculum coherence and the spectre of practice. Issue 8 (17th November 2022) - Muller, Johan
ABSTRACT: This paper will re-visit the origins and early use in South African curriculum writing of the concept of 'coherence'; it will go on to show how Suellen Shay and her colleagues fleshed out the concept and created an instrument for its empirical analysis; it will then step back and examine the contribution and some problems that were brought to light; examine briefly how Shay's later work continued to wrestle with the notion of 'practice', particularly in light of curricula that were judged to display conceptual coherence; and will suggest one possible solution in the seminal paper by Bernstein (2000). Finally, the paper will reflect on two implicit definitions of 'curriculum', a 'strict' one and an 'extended' one and suggest why they should be distinguished.